Evidence from HIV sequencing for blood-borne transmission in Africa - David Gisselquist; Simon Collery (Journal of Public Health in Africa)
Background: The consensus view that heterosexual transmission dominates human immunodeficiency viruses (HIV) epidemics in sub-Saharan Africa survives side-by-side with surveys and studies reporting infections in children with HIV-negative mothers, in virgins, and in adolescents and adults who claim no possible sexual exposure to HIV.